(untitled) (Journal of Advanced Research in Social Sciences, 2025)
Learning spaces can be conducive to student wellbeing. The study presents the perspectives of students in Malta about present and possible learning spaces. Previous research focuses on the importance of including students in the design of learning spaces. It also presents schools as one of the most central spaces for positive holistic development, thus suggesting participatory designing of learning spaces. The research presented in this paper is based on three principles as outlined by Barrett et al. (2015) which are naturalness, individualisation and stimulation, which make a difference on the impact of the learning space. For the research about learning spaces in Maltese state schools, I made use of an interpretivist paradigm guiding the qualitative methodology. The research included sixteen focus groups, held during Personal, Social and Career Development (PSCD) subject, with students attending Maltese primary (aged 8-10years) and secondary schools (11-16years), chosen through purposive sampling. In total, there were six classes with primary school students and ten classes with students from middle and secondary schools. All students who participated were given an information sheet and their parents or guardians signed a consent form ensuring that they are not subject to harm, their identity would remain anonymous and that they can stop their participation. Results from this research show that students were negative about existing learning spaces. This research confirmed the importance of the dimensions presented in the study by Barrett et al. (2015) and identified another dimension – innovative learning spaces. Evidence from this research also shows that a learning space should have adequate lighting, sound, temperature, relaxing surrounding colours, link to nature and should allow ownership, flexibility, and connection. This paper is particularly inspiring for policymakers as it demonstrates the significance of learning spaces in influencing the happiness and wellbeing of students.